Implementasi Kebijakan Shopee Dalam Melindungi Driver Shopeefood Terhadap Orderan Fiktif Di Kota Surabaya - Muhammad Haidar Ali; Waluyo Waluyo (Journal Kompilasi Hukum, 2026)
This study aims to examine how legal protection and legal certainty are provided by PT Shopee International Indonesia to ShopeeFood drivers in dealing with the issue of fictitious orders on the ShopeeFood service. The background for this research stems from the problem of fictitious orders, which are increasing day by day, causing tangible losses for ShopeeFood drivers. This study employs an empirical legal research method by applying a legislative approach, a conceptual approach, and a case study approach. Legal sources include primary legal sources, secondary legal sources, and non-legal sources. Data collection was conducted through field research and a literature review. The results of this study indicate that PT Shopee Internasional Indonesia provides legal protection to ShopeeFood drivers through both preventive and repressive measures. However, in practice, these measures have not yet been effective in providing legal protection and certainty for ShopeeFood drivers.